Early Functional Connectivity Predicts Recovery from Visual Field Defects after Stroke - Kim, Yong-Hwan (J Stroke, 2019)
BACKGROUND AND PURPOSE: We aimed to assess whether early resting-state functional connectivity (RSFC) changes measured via functional magnetic resonance imaging (fMRI) could predict recovery from visual field defect (VFD) in acute stroke patients. METHODS: Patients with VFD due to acute ischemic stroke in the visual cortex and age-matched healthy controls were prospectively enrolled. Serial resting-state (RS)-fMRI and Humphrey visual field (VF) tests were performed within 1 week and at 1 and 3 months (additional VF test at 6 months) after stroke onset in the patient group. The control group also underwent RS-fMRI and a Humphrey VF test. The changes in RSFCs and VF scores (VFSs) over time and their correlations were investigated. RESULTS: In 32 patients (65±10 years, 25 men), the VFSs were lower and the interhemispheric RSFC in the visual cortices was decreased compared to the control group (n=15, 62±6 years, seven men). The VFSs and interhemispheric RSFC in the visual cortex increased mainly within the first month after stroke onset. The interhemispheric RSFC and VFSs were positively correlated at 1 month after stroke onset. Moreover, the interhemispheric RSFCs in the visual cortex within 1 week were positively correlated with the follow-up VFSs. CONCLUSIONS: Interhemispheric RSFCs in the visual cortices within 1 week after stroke onset may be a useful biomarker to predict long-term VFD recovery.